Gingivektomi Pada Enlargement Gingiva Karena Malposisi Gigi Individual - Salwa Safira; Ariyani Faizah (Jurnal Sehat Indonesia (JUSINDO), 2026)
Gingival enlargement is defined as a common clinical sign of gingiva caused directly by plaque that causes gingival inflammation. Gingivectomy is a procedure that can be performed on patients with gingival enlargement. This case report describes the management of gingival enlargement in a case of tooth 42 due to individual tooth malposition. A 20-year-old male patient came to Soelastri Dental and Oral Hospital in Surakarta complaining of swollen gums. The complaint was felt in the upper and lower front gums. The patient was unaware of the swelling, had never received treatment, and did not experience any pain. Gingival treatment for this patient began with phase 1 periodontal therapy followed by gingivectomy. The gingivectomy treatment in this case used a scalpel instrument and the results were effective in reducing the patient's gingival enlargement. The patient was advised to undergo further orthodontic treatment to correct individual tooth malposition.